2009
DOI: 10.1177/0539018409106199
|View full text |Cite
|
Sign up to set email alerts
|

Emotion and colour across languages: implicit associations in Spanish colour terms

Abstract: Abstract. This study explores the reasons why colour words and emotion words are frequently associated in the different languages of the world. One of them is connotative overlap between the colour term and the emotion term. A new experimental methodology, the Implicit Association Test (IAT), is used to investigate the implicit connotative structure of the Peninsular Spanish colour terms rojo (red), azul (blue), verde (green) and amarillo (yellow) in terms of Osgood's universal semantic dimensions: Evaluation … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

7
63
0
3

Year Published

2012
2012
2024
2024

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 62 publications
(73 citation statements)
references
References 39 publications
7
63
0
3
Order By: Relevance
“…Brighter and more chromatic colors were rated as more pleasant; darker and more chromatic colors were rated as more arousing; and darker and more saturated colors were rated as more dominant. Similar associations have been reported in other studies using physical color samples and color concepts . These associations between color dimensions and emotion dimensions seem to hold cross‐culturally with, for example, lighter colors being evaluated as more positive than darker colors .…”
Section: Introductionsupporting
confidence: 86%
See 1 more Smart Citation
“…Brighter and more chromatic colors were rated as more pleasant; darker and more chromatic colors were rated as more arousing; and darker and more saturated colors were rated as more dominant. Similar associations have been reported in other studies using physical color samples and color concepts . These associations between color dimensions and emotion dimensions seem to hold cross‐culturally with, for example, lighter colors being evaluated as more positive than darker colors .…”
Section: Introductionsupporting
confidence: 86%
“…Similar associations have been reported in other studies using physical color samples 17 and color concepts. 18,19 These associations between color dimensions and emotion dimensions seem to hold cross-culturally with, for example, lighter colors being evaluated as more positive than darker colors. 20,21 Other lines of research focused on color associations with more specific discrete emotions.…”
Section: Introductionmentioning
confidence: 96%
“…The most frequently mentioned colour before the intervention was black (31.40%) followed by white (19.35%), whereas after the intervention, the most frequent colour was white (23.12%) followed by black (17.66%) and red (16.62%). Black is a colour that almost universally has a negative connotation attached to it in contrast to white, which usually has positive connotations (Soriano & Valenzuela, ).…”
Section: Resultsmentioning
confidence: 99%
“…As the focus of the current study is on the semantics of the green colour, only the findings related to the term green are discussed. Soriano and Valenzuela [15] studied the connotative structures of red, blue, green and yellow in Spanish with regard to Osgood's semantic dimensions, namely Evaluation (good-bad), Activity (excited-relaxed) and Potency (strong-weak) to explore the reasons behind the association between colour terms and emotion words. They showed that green has positive evaluation and low activity despite its conventional association with envy by means of metonymy.…”
Section: Literature Reviewmentioning
confidence: 99%
“…The literature on colour categorization and semantic extension of colour terms across cultures show that there are commonalities and variations in meanings of colour terms and in the ways individuals categorize colours across languages [15] [16] [17]. This diversity is mostly the usual outcome of semantic change.…”
Section: Introductionmentioning
confidence: 99%